1998
DOI: 10.1007/s004380050798
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of 5-methylcytosine residues in Nicotiana tabacum 5S rRNA genes by genomic sequencing

Abstract: Genomic sequencing was used to localise 5-methylcytosine residues in individual DNA strands of 5S rRNA genes in tobacco. The density of methylation along the sequence was high in both strands, exceeding the average methylation density of the tobacco genome. Besides methylation of CG and CNG sequences, considerable amounts of mC were found in non-symmetrical sites. Among 69 sequenced clones obtained from leaf DNA we did not detect any non-methylated clone, and Southern blot hybridisation analysis also failed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(33 citation statements)
references
References 25 publications
1
32
0
Order By: Relevance
“…After washing under high-stringency conditions, the hybridisation bands were visualized with a PhosphorImager (Storm, Molecular Dynamics, Sunnyvale, CA), and the data were processed by ImageQuant software (Molecular Dynamics). The probes were a 220-bp PCR product derived from the 3' end of the 26S rRNA gene of tobacco [23] and a cloned ~120 bp of the 5S genic region, also from tobacco [24]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After washing under high-stringency conditions, the hybridisation bands were visualized with a PhosphorImager (Storm, Molecular Dynamics, Sunnyvale, CA), and the data were processed by ImageQuant software (Molecular Dynamics). The probes were a 220-bp PCR product derived from the 3' end of the 26S rRNA gene of tobacco [23] and a cloned ~120 bp of the 5S genic region, also from tobacco [24]. …”
Section: Methodsmentioning
confidence: 99%
“…The positions of the PCR primers are depicted in Figure 1. The primers were: 5SLf (5'-CCTGGGAATTCCTCGTGTT-3'), 5SLr (5'-TGCGTTAAAGCTTGTATGATCGCAT-3') from [24], and 26Sf (5'-GAATTCACCCAAGTGTTGGGAT-3'), originally called P1 in [23]. The PCR profile used for amplification was: initial denaturation at 94°C for 3 min followed by 35 cycles of 20 s at 94°C, 30 s at 57°C and 30 s at 72°C; and a final extension step at 72°C, 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…The endogenous family of 5S rRNA genes was immunoprecipited with anti H3K9me2 but not H3K4me3 ( Fig. S3C ) consistent with their heterochromatic nature 50 and heavy DNA methylation 51 . Actin genes showed intermediate signals with both euchromatic and heterochromatic signals, whereas in Arabidopsis, actin genes were strictly euchromatic 52 .…”
Section: Resultsmentioning
confidence: 76%
“…The NTS units seem to have been subject to rapid evolution. In the natural tobacco allotetraploids, Nicotiana tabacum [19] and Nicotiana rustica [20], two 5S rDNA families were identified that differed in the length of the NTS sequence. Similar differences in the NTS units have been described in 5S rDNAs from fishes such as Oreochromis niloticus , Oncorhynchus mykiss , Coregonus [21], Merluccius [10], and Rhizoprionodon sharks [22].…”
Section: Discussionmentioning
confidence: 99%